Pengaruh Suhu Terhadap Karakteristik Arang Hasil Pirolisis Kulit Kolang-Kaling (Arenga pinnata) - Yuniarti Yuniarti; Eka Megawati; Ana Dewi; Debora Ariyani; Meita Rezki Vegatama; Ain Sahara (Politeknik Negeri Malang, 2022)
ABSTRACTSugar palm plants are included in the top ten plantation commodities in East Kalimantan. So far, kolang-kaling fruit peel waste has not been widely used, except for fertilizer. Palm peel waste has a non-uniform texture, but the inside is hard, so it can be used to make charcoal. Charcoal is made by pyrolysis process and can be used as raw material for briquettes as a new renewable energy source. This study aims to obtain biochar as a raw material for making briquettes with the highest calorific value through the pyrolysis process. The manufacture of biochar begins with the drying process of the raw materials and then proceeds with heating the sample in a pyrolysis reactor for 1 hour. The process takes place with the constant variable is the sample weight of 500 g and the heating time for 1 hour, and the variable that changes is the combustion temperature. Pyrolysis was carried out at temperatures of 200 °C, 250 °C, 300 °C, 350 °C, and 400 °C. The mass of charcoal obtained was 487.23 g, 438.37 g, 402.03 g, 318.1 g and 278.84 g. The resulting calorific value is 4158.7 cal/g, 4432.5 cal/g, 4620.2 cal/g and 4840.7 cal/g. The ash content were 12.01%, 14.64%, 14.99%, 15.25% 21.98%, respectively. Volatile Matter obtained 76.50%, 69.67%, 61.68%, 56.71%, 47.15%. While the fixed carbon biochar is 0.80%, 8.93%, 9 78%, 11.30%, 16.31%. The characteristics of the pyrolysis biochar are seen by proximate testing. Biochar with the highest calorific value was obtained at a temperature of 400 °C, namely 4840.7 cal/g.Keywords: Palm fruit peel, Calorific value, Pyrolysis, Charcoal